Case Report: First Report and Phylogenetic Analysis of Porcine Astroviruses in Chile - Flores, Carlos; Ariyama, Naomi; Bennett, Benjamín; Mena, Juan; Verdugo, Claudio; Mor, Sunil; Brito, Barbara; Ramírez-Toloza, Galia; Neira, Victor (Frontiers in Veterinary Science, 2021)
Porcine Astrovirus (PoAstV) causes mild diarrhea in young pigs and is considered an emerging virus in the swine industry worldwide. PoAstV has high genetic diversity and has been classified into five genetic lineages, PoAstV1-5. In Chile, only human astroviruses have been reported. This study aimed to determine the presence and genetic diversity of PoAstV circulating in intensive pig farms in Chile. Seventeen Chilean intensive swine farms from Valparaíso, Metropolitana, O'Higgins, Ñuble and Araucanía regions were sampled. A selection of oral fluid and fecal material samples from 1-80 days-old pigs were collected and analyzed using next-generation sequencing. The circulation of PoAstV was confirmed in all studied farms. We obtained complete or partial sequences of PoAstV-2 (n=3), PoAstV-4 (n=2), and PoAstV-5 (n=7). In 15 out of 17 farms, we detected more than one lineage co-circulating. Phylogenetic analyses grouped the seven PoAstV-5 strains in a monophyletic cluster, closely related to the United States PoAstV-5 strains. The three PoAstV-2 were located into two separate sub-clusters. PoAstV-4 sequences are also grouped in two different clusters, all related to Japanese strains. The results evidence the high occurrence and diversity of PoAstV in Chile; however, the lack of reference sequences was an important limitation to establish local evolution and regional comparison of its diversity. This is the first contribution of PoAstV genomes in Latin America, more studies are needed to understand the diversity and impact of PoAstV in swine health.